Contextual Learning Models In PKN Learning - Fitri, Nur Laily; Nasution, Saidatul Fadhillah; Nasution, Abdul Gani Jamora (Yayasan Pendidikan Islam Akmalia, 2023)
Citizenship education (civic education) in Indonesia is placed as a field of study that carries a national mission to educate the life of the Indonesian people through the corridor of